Analysis of the Family Hope Program - Novy Arthamevia; Hendra Sukmana (Universitas Muhammadiyah Sidoarjo, 2022)
The purpose of this study was to describe and analyze the family of hope program along with the obstacles in the family of hope program in Sidoarjo Regency. This research is based on the problem of assistants who carry out socialization only once every three months and there are still many PKH recipients who do not understand their rights and obligations. The research method used is qualitative research. The data collection technique is by means of in-depth interviews, observations and relevant literature studies with one key informant, namely the Village PKH assistant and four supporting informants including the District PKH coordinator, village secretary, and PKH assistance recipient communities. The analysis technique in this study uses a qualitative type that refers to the theory of Miles and Huberman. The results showed that the analysis of the family of hope program in Sidoarjo, namely, first, the achievement of goals. The achievement measure is said to have not been achieved because the targets for accepting PKH members are still not on target and the process of managing the aid index for PKH recipients is still not right. The second is integration, the size of integration is said to be not right because there has been no delivery of skills for PKH members in socializing with PKH facilitators. Third, adaptation, PKH facilitators are quite good and can adapt to PKH members and their environment. Keywords – ;